Mathematical Modelling of Micronutrient Recovery from Vegetable Oil by Silica-based Adsorption: Vitamin E from Palm Fatty Acid Distillate - Ari Diana Susanti; Wahyudi Budi Sediawan; Sang Kompiang Wirawan; Budhijanto Budhijanto (Program studi Teknik Kimia UNS, 2017)
Mathematical modelling on kinetics of batch adsorption of vitamin E separation from palm fatty acid distillate (PFAD) has been set-up and then applied for literature experimental data. Since the sizes of adsorbent particles used are usually relatively small, the concentration in the particles is assumed to be uniform. Hence, the adsorption rate is controlled by the rate of solute mass transfer from the bulk fluid to the surface of particles. In this model, the rate of mass transfer is assumed to be proportional to the concentration deviation from the equilibrium state. Meanwhile, the equilibrium models applied were coefficient distribution, Freundlich, and Langmuir with the values of the parameters obtained from literature data. It turned out that the model set-up can quantitatively describe the experimental kinetics data from literature. The value of mass transfer coefficient per unit adsorbent mass (kca) is obtained by curve fitting. It is also observed that the model proposed quantitatively describes the batch adsorption process well. The three equilibrium models applied are suitable for the mathematical modelling. Adjustment of the values of equilibrium isotherm parameters from literature significantly improves the accuracy of the model.